Electrochemical Sensitivity Improvement by the Cooperation between Pt and Ru for Total Antioxidant Evaluation in Natural Extracts - Carvalho Diniz, Gustavo (2023)
“Herein, a straightforward electrochemical method was used to evaluate the total phenolic antioxidant capacity in natural extracts prepared from pomegranate, hibiscus, and pitaya. In light of this, the well-known electrochemical index (EI), a screening protocol for natural antioxidant properties evaluation, was determined using differential pulse voltammetry. Initially considering rutin and catechin as standards, we found that the system’s sensitivity greatly increased by using platinum (Pt) and platinum/ruthenium (Pt/Ru) nanoparticles (NPs) immobilized on Vulcan XC-72 to modify screen-printed carbon electrodes (SPCEs). When such modifications were applied to natural fruit/plant extracts, their electrochemical ability proved highly superior to the bare SPCE, even considering a very small amount of materials for electrode preparation. However, with an optimized ratio, the bimetallic counterpart was more sensitive to detection. When the pomegranate extract was used, for example, EI values of 52.51 ± 6.00 and 104.79 ± 6.89 µA/V were obtained using Pt and Pt/Ru (with an optimized ratio) electrocatalysts, showing the remarkable sensitivity increase obtained in our bimetallic protocol. Thus, based on physicochemical and electrochemical characterizations, we found that the ruthenium content was essential for the achievements. In due course, XPS analysis suggested that the Pt2+/Pt0 species ratio could have improved the system’s sensitivity, which significantly changed when ruthenium was used in the material. “